Effect of trace mineral (mineral capsule) supplementation on nutrient utilization and rumen fermentation pattern in Sahiwal cows (Bos indicus) - TIWARI, S P; JAIN, R K; MISHRA, U K; MISHRA, O P; PATEL, J R; RAJAGOPAL, S (The Indian Journal of Animal Sciences, 2013)
The effect of supplementation of trace minerals, viz. Cu, Co, Mn and Zn on the utilization of nutrients and rumen fermentation pattern was studied in 16 Sahiwal cows. They were divided at random into 2 groups of 8 animals each. All the animals were individually offered green berseem and para grass (Brachiaria mutiea) ad lib. and standard concentrate mixture 3 kg/day. An additional amount of 1 kg crushed maize grain/day per animal was offered in both the groups. Group 1 was kept as control while group 2 was supplemented with Cu, Co, Mn and Zn in the form of gelatinised capsule (3.34,0.442, 7.62 and 125.73 mg/day) respectively. The experiment lasted for 120 days. Digestion trial was conducted on 8 cows of 4 in each group. The intake of DCP and TDN in groups 1 and 2 were 0.913, 0.903 and 6.33, 5.58 kg/day which were statistically nonsignificant (P<0.05). However, the intake of DM and DCP (kg/100 kg bwt) was significantly (P<0.05) higher in mineral supplemented group’ as compared to control group. Similarly digestibilities of OM, NFE and hemicellulose were significantly higher in group 2 than that of group 1. The concentration of TCA ppt-N in SRL was also significantly higher (P<0.05) in group 2 as compared to group I, whereas NH3-N concentration was significantly (P<0.05) higher in group I than that in group 2, suggesting an enhanced activity ofNH3 utilization by rumen microbes. Mineral supplementation, however, had increased the blood sugar to almost double Le. from 32.90 to 65.53 mg/100ml, and TVF A concentration from 134 to 140 meq/litre. The other rumen parameters, viz. pH and NPN, total Nand TCA-ppt N were not affected. The Hb concentration was significantly higher in trace mineral supplemented group compared to control suggesting better utilization of related minerals and protein for the synthesis of Hb. It may be concluded that supplementation of Cu, Co, Mn and Zn at 1.75,0.058, 1 and 16.5ppm, respectively, in the ration of Sahiwal cows appears to be adequate for better nutrient utilization, rumen fermentation pattern and microbial activity in mature cows.